2024
DOI: 10.1038/s41419-024-06453-8
|View full text |Cite
|
Sign up to set email alerts
|

BACH2-mediated CD28 and CD40LG axes contribute to pathogenesis and progression of T-cell lymphoblastic leukemia

Min Feng,
Bailing Zhang,
Guilan Li
et al.

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive subtype of ALL characterized by its high heterogeneity and unfavorable clinical features. Despite improved insights in genetic and epigenetic landscapes of T-ALL, the molecular mechanisms that drive malignant T-cell development remain unclear. BTB and CNC homology 2 (BACH2) is a lymphoid-specific transcription repressor recognized as a tumor suppressor in B-cell malignancies, but little is known about its function and regulatory network in T-ALL. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…The research did not directly find a connection between CD40LG and glaucoma or its clinical implications for treatment. However, studies on BACH2’s role in immune response regulation and T-cell lymphoblastic leukemia progression emphasized the importance of understanding molecular pathways involving CD40LG for potential therapeutic targets ( Feng et al, 2024 ). While specific studies on glaucoma were not identified, exploring TEK mutations, especially in primary congenital glaucoma (PCG), sheds light on genetic contributions to ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The research did not directly find a connection between CD40LG and glaucoma or its clinical implications for treatment. However, studies on BACH2’s role in immune response regulation and T-cell lymphoblastic leukemia progression emphasized the importance of understanding molecular pathways involving CD40LG for potential therapeutic targets ( Feng et al, 2024 ). While specific studies on glaucoma were not identified, exploring TEK mutations, especially in primary congenital glaucoma (PCG), sheds light on genetic contributions to ocular diseases.…”
Section: Discussionmentioning
confidence: 99%